Mali : Technical Assistance Report: Continued Modernization of the Malian Tax System and Administration. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Assistance Report focuses on continued modernization of the Malian tax system and administration. The crisis that has afflicted Mali since 2012 has had an adverse economic impact, reflected in a 25 percent decline in government resources and negative growth of -1.2 percent. Despite the difficult context, the combination of reduced investment expenditure, improved tax collection, reduced subsidies, and increased taxes on petroleum products served to contain the budget deficit at 1.3 percent of GDP. In regard to increasing own resources, the government is committed to increasing tax receipts to reduce dependence on foreign aid.